Opportunities and challenges for physical rehabilitation with indigenous populations. (23rd September 2020) - Lin, Ivan; Coffin, Juli; Bullen, Jonathan; Barnabe, Cheryl
Abstract : Indigenous peoples internationally have low access to physical rehabilitation, despite high needs. Achieving equitable outcomes requires reorientating services to be culturally appropriate for Indigenous peoples. Abstract: Indigenous peoples in colonised countries internationally experience a disproportionately high burden of disease and disability. The impact of many of these conditions, such as musculoskeletal pain, can be ameliorated by participating in physical rehabilitation. However, access by Indigenous peoples to physical rehabilitation is low. Overcoming barriers for Indigenous peoples to access high-quality, effective, culturally secure physical rehabilitation should be a priority. Physical rehabilitation outcomes for Indigenous peoples can be enhanced by addressing health system, health service, and individual clinician-level considerations. System-level changes include a greater commitment to cultural security, improving the funding of physical rehabilitation to Indigenous communities, building the Indigenous physical rehabilitation workforce, and developing and using Indigenous-identified indicators in quality improvement. At the health service level, physical rehabilitation should be based within Indigenous health services, Indigenous people should be employed as physical rehabilitation professionals or in allied roles, and cultural training and support provided to the existing physical rehabilitation workforce. For clinicians, a focus on cultural development and the quality of communication is needed. Indigenous ill-health is complex and includes societal and social influences. These recommendations offer practical guidance toward fair, reasonable, and equitable physical rehabilitation outcomes for Indigenous peoples.